Pengaruh E-Procurement Terhadap Efektivitas Pengadaan Barang Dan Jasa (Studi Pada UKPBJ SETDA Kota Gunungsitoli) - Mendrofa, Danieli; Gea, Jeliswan Berkat Iman Jaya; Bate’e, Maria Magdalena; Zebua, Serniati (LPPM Universitas HKBP Nommensen, 2024)
One of the public services that utilizes the e-government system to achieve good governance in Indonesian Government agencies is services in the procurement of government goods / services. Procurement of goods and services carried out by the government is very instrumental in the success of national development in order to improve public services in various regions, specifically in the Gunungsitoli City Government. The purpose of this study is to determine whether there is an effect of e-procurement; to find out how significant the effect of e-procurement; and to find out how the effect of e-procurement on the effectiveness of the procurement of goods and services at UKPBJ SETDA Gunungsitoli City. This research was conducted using quantitative research methods, to see and statistically assess how e-procurement influences the effectiveness of the procurement of goods / services, whose data collection was carried out through distributing closed questionnaires and the results were processed through SPSS 22. Based on the results of research that has been carried out by conducting hypothesis testing through the t test (partial), the results obtained tcount (5.651)>ttable (1.6794) with a significance value of 0.000 <0.005, which means that there is an influence of e-procurement on the effectiveness of government procurement of goods / services at UKPBJ Gunungsitoli City.